(untitled) (Актуальні проблеми психології в закладах освіти, 2019)
Parental alienation syndrome (PAS) is a theory that has been the subject of much debate. Moreover, the sheer magnitude of parental alienation (PA) shows that this is a significant social problem. Not only does this study aim to analyze the causes of parental alienation, but it also aims to present the role and importance of the psychotherapy of possibilities in treating PA as a phenomenon related to a wide range of familial situations. According to a study, conducted on 15 married couples (all in conflict), the psychotherapy of possibilities does positively affect and soften PA behaviors. Moreover, it was indicated that the study subjects’ psychological and somatic problems were reduced. The study demonstrated that PA results not from psychological traits. The causes and motives of becoming a couple also prove to be crucial. For that reason, the psychotherapy of possibilities can be effectively applied in the process of dealing with the parental alienation syndrome.